2007
DOI: 10.2113/gscanmin.45.2.281
|View full text |Cite
|
Sign up to set email alerts
|

THE STATE OF HYDRATION OF Ca-EXCHANGED MONTMORILLONITE AT A DEPTH OF 2 2.7 KILOMETERS

Abstract: Monte Carlo simulations in NP zz T and VT ensembles of the hydration of Ca-saturated Wyoming-type montmorillonite show that one-layer Ca-exchanged montmorillonite hydrate with a d 001 of 12.11 Å is stable at 353 K, 300 bar, and-7.21 kcal/mol potential. Two-and three-layer hydrates do not appear stable. At 353 K and 625 bar, the one-layer hydrate is nearly stable. In the interlayer space, molecules of H 2 O are clustered on the interlayer midplane, alternatively oriented with their protons toward the siloxane s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…There is a large body of experimental [ Mooney et al ., ; Chiou and Rutherford , ; Cuadros , ; Morodome and Kawamura , ; Woodruff and Revil , ] and modeling studies [ Skipper et al ., ; Chang et al ., ; Chavez et al ., ; Meleshyn and Bunnenberg , ; Ferrage et al ., , ; De Pablo et al ., ] on interlayer distances in montmorillonite with increasing relative humidity or water vapor pressure. While the conditions in these studies differ from ours, they are useful in helping to understand the role of the interlayer cation in the swelling mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a large body of experimental [ Mooney et al ., ; Chiou and Rutherford , ; Cuadros , ; Morodome and Kawamura , ; Woodruff and Revil , ] and modeling studies [ Skipper et al ., ; Chang et al ., ; Chavez et al ., ; Meleshyn and Bunnenberg , ; Ferrage et al ., , ; De Pablo et al ., ] on interlayer distances in montmorillonite with increasing relative humidity or water vapor pressure. While the conditions in these studies differ from ours, they are useful in helping to understand the role of the interlayer cation in the swelling mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the above studies, which were performed at low pressure, some experimental [ van Gross and Guggenheim , ; Wu et al , ] and modeling studies [ Chavez et al , ; Monsalvo et al , ; De Pablo et al , ; Vidal and Dubacq , ] have been used to investigate the stability of the water structures in Ca‐, Na‐, and K‐montmorillonite at higher temperature and pressure. While results are somewhat inconsistent, the general trend confirms that K‐montmorillonite dehydrates at lower pressure and temperature than Na‐, Ca‐, and Mg‐montmorillonite.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Mg-smectite (such as saponite), the Mg cations derived from dissolution of the serpentine together with Ca cations derived from adjacent shale lithologies are primary cations occupying the hydrated interlayer sites. Hydration phase diagrams and molecular simulations by Monte Carlo modelling of smectite indicate the predicted structure of hydrated Ca-bearing water layers at 2.7 km crustal depth should be the 1 water-layer structure with a lattice thickness of 1.18 nm (De Pablo et al, 2007). Based on the location of slip planes observed at the crystal scale, it is confirmed that slip occurs primarily along the Mg-and Ca-occupied hydrated interlayers whereby displacements are spaced at 3e5 lattice layers apart (Fig.…”
Section: Model Of Clay Fabric Evolutionmentioning
confidence: 94%
“…They concluded that the seal quality would be enhanced as a result of interaction of CO 2 with the overlying shale. De Pablo et al (2007) predicted the hydration state of Ca ++ Mt at typical sequestration depths based on Monte Carlo simulations; they predict that the clay mineral would maintain a one water layer of state of hydration at temperature and pressure conditions of typical storage reservoirs.…”
Section: Introductionmentioning
confidence: 99%